Gender Gaps in Digital Enterprise:The Role of Care Burden and Human Capital in Indonesia - Setyanti, Axellina Muara; Setiawan, Andi Tri (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2026)
This study aims to analyze gender disparities in digital enterprise participation in Indonesia, with particular emphasis on the roles of caregiving burdens and human capital. Although digitalization is often viewed as a force that can promote equality in entrepreneurship, empirical evidence on how gender and household constraints shape participation in digital enterprises remains limited. Using microdata from the 2024 National Socioeconomic Survey (SUSENAS), digital enterprise is defined as engagement in business activities supported by the use of digital technology. A binary logistic regression model is employed to estimate the probability of digital enterprise participation, followed by rural–urban subgroup analysis to capture spatial heterogeneity. The results reveal a pronounced gender gap, with women significantly less likely to participate in digital enterprises than men after controlling for household and demographic characteristics. However, caregiving responsibilities, proxied by the presence of children under five years old, are positively associated with digital enterprise participation, suggesting that digital entrepreneurship may serve as a flexible work strategy under childcare constraints. Human capital and digital access also play important roles in shaping participation. Education increases the likelihood of digital enterprise engagement, particularly in urban areas, while handphone ownership emerges as the strongest predictor across all contexts. Rural–urban estimates further show that the gender gap is more pronounced in rural areas, reflecting the interaction between gender norms and spatial inequality.